Deregulation of the Kallikrein Protease Family in the Salivary Glands of the Sjögren’s Syndrome ERdj5 Knockout Mouse Model - Moustardas, Petros; Yamada-Fowler, Naomi; Apostolou, Eirini; Tzioufas, Athanasios G.; Turkina, Maria V.; Spyrou, Giannis (Frontiers in Immunology, 2021)
Introduction The purpose of this study was to identify differentially expressed proteins in salivary glands of the ERdj5 knockout mouse model for Sjögren’s syndrome and to elucidate possible mechanisms for the morbid phenotype development. At the same time, we describe for the first time the sexual dimorphism of the murine submandibular salivary gland at the proteome level. Methods We performed Liquid Chromatography/Mass Spectrometry in salivary gland tissues from both sexes of ERdj5 knockout and 129SV wildtype mice. The resulting list of proteins was evaluated with bioinformatic analysis and selected proteins were validated by western blot and immunohistochemistry and further analyzed at the transcription level by qRT-PCR. Results We identified 88 deregulated proteins in females, and 55 in males in wildtype vs knockout comparisons. In both sexes, Kallikrein 1b22 was highly upregulated (fold change>25, ANOVA p<0.0001), while all other proteases of this family were either downregulated or not significantly affected by the genotype. Bioinformatic analysis revealed a possible connection with the downregulated NGF that was further validated by independent methods. Concurrently, we identified 416 proteins that were significantly different in the salivary gland proteome of wildtype female vs male mice and highlighted pathways that could be driving the strong female bias of the pathology. Conclusion Our research provides a list of novel targets and supports the involvement of an NGF-mediating proteolytic deregulation pathway as a focus point towards the better understanding of the underlying mechanism of Sjögren’s syndrome.